What is Christian Philosophy and Who is a Christian Philosopher? Richard Schaeffler as an Example - Vasek, Martin (New blackfriars, 2026)
The study will focus on the German philosopher, Richard Schaeffler (1926–2019). Schaeffler wanted to create a new transcendental philosophy by developing Kant’s thought and thereby a new form of Christian philosophy. In his texts, he not only sketched the contours of a possible Christian transcendental philosophy, but his philosophy is already just such a philosophy. The aim of the study is to answer two questions: How did Schaeffler understand Christian philosophy, and what is specific about his Christian philosophy? In answering these questions, I will briefly compare Richard Schaeffler and Gianni Vattimo, who considered his philosophy to be Christian. The specific character of Christian philosophy – not only of Schaeffler’s – will be highlighted against the background of Vattimo’s philosophy, and the limits and deficiencies of Vattimo’s ‘Christian philosophy’ will be shown against the background of Schaeffler’s thought.